Efisiensi Teknis Usahatani Kentang di Desa Sarimukti Kecamatan Pasirwangi Kabupaten Garut - Ashillah, Regita Cahyani Putri; Rachmawati, Erna; Rochdiani, Dini; Trimo, Lucyana (Universitas Galuh, 2024)
Garut Regency was main centers of potato production in West Java however potato productivity tended to be low because the potential productivity of potatoes was not achieved. The aims of this study were to; 1) analyze the effect of production factors on potato farming production, 2) analyze the level of technical efficiency of potato farming. The sample size was 59 farmers and taken using simple random sampling from a population of 69 farmers. The analytical method used was the stochastic frontier Cobb-Douglas production function. This research was conduct at Sarimukti Village, Pasirwangi Subdistrict as the one of potato production center in Garut District using a survey method. The result showed that; 1) the production factors of land area and seeds had a positive and significant effect on potato farming production, 2) the value of technical efficiency of potato farming tended to be low at 69%. To increase technical efficiency, it was important to implement efficiency-based potato farming activities in accordance with the technical guidelines for potato cultivation.